Understanding youth STEM interest pathways within a single community: the Synergies project. Issue 4 (1st October 2016) - Falk, John H.; Staus, Nancy; Dierking, Lynn D.; Penuel, William; Wyld, Jennifer; Bailey, Deborah
ABSTRACT: The dramatic decline in youth interest in science, technology, engineering and mathematics (STEM) during adolescence, both in the USA and internationally, has been a phenomenon of societal concern for several decades. The Synergies project was launched to help deal with this issue. In this paper, we report findings from the first two years of our longitudinal survey research. We sought to understand the nature of the STEM-related interests of 10-/11-year-old youth living in a single urban community and the factors that seem to influence whether these various dimensions of interest increase, stay the same or diminish over time. We found that interest in three STEM dimensions—earth/space science, life science and technology/engineering—increased significantly for youth between the ages of 10/11 and 11/12 years. In contrast to the increase in STEM interest, there was a decrease in participation rates in a variety of STEM activities for the same individuals over the same time frame. We found no correlations between STEM interest and teacher or leader variables. We also found strong positive correlations between all four STEM dimensions and most of the interest-related variables including STEM knowledge, science relevance and science enjoyment. Collectively, this research provides new insights into the nature and processes of youth STEM interest pathways. We are using this empirical foundation with our community partners to improve practice.